The Exercise Increase Nuclear Factor E2-Related Factor 2 (Nrf2) And Correlate With Aging: Literature Review - Sheriman, Erynne Gracia Monica; Hartono, Yessy; Fernanda, Callista; Maya, Noor Jumay; Widjaja, Stella; Juhanna, Indira Vidiari; Adiatmika, I Putu Gede (Sport and Fitness Journal; Vol 10 No 2 (2022): Volume 10, No. 2, May 2022DO - 10.24843/spj.2022.v10.i02.p08, 2022)
Aging is a natural life process. Aging is associated with oxidative stress that results in decreased function and structural organs, including mitochondria. Nuclear Factor E-2 related factor 2 (NRF2) is the master regulator of antioxidants. NRF2 can suppress the damage caused by oxidative stress. Our purpose is to see the correlation between exercise in improving NRF2 and efficacy to prevent aging. This paper is a literature review journal. Sources of data obtained for this journal are through databases of scientific information sources such as Proquest, Pubmed, Mendeley, Elsevier, Department of Sports Medicine, Medical Faculty of Uludag University, Nature Publishing Group, American Physiological Society, and Frontiers Media S.A. We use a data collection strategy using keywords: NRF2, aging, exercise to find journals/articles to be reviewed, with a limit of 5 to 10 years of the latest articles. During exercise, high-intensity interval training aerobic, NRF-2 increases peripheral blood circulation. Exercise causes temporary oxidative stress that will cause an adaptive mitochondrial response (mitohormesis) which will improve function and be resistant to stress. With increased mitochondrial function, organ damage can be prevented, improve skeletal muscle performance, and extend lifespan. NRF2 deficiency is associated with an increase in free radicals that will affect organ health, as well as a decrease in skeletal muscle function and mass. This review summarized exercises to increase NRF2, NRF2 function, and correlation with aging. The Limitation of this review is we used only research published last 10 years. The method limitation is a risk of bias.